The chameleon of mens rea and the shifting guises of culture-specific genocidal intent in international criminal proceedings. Issue 4 (1st October 2016) - Dojčinović, Predrag
ABSTRACT: This article examines the significance of the mens rea -related evidence present in the specific language and discourse identified in the records of the International Military Tribunal, the International Criminal Tribunal for Rwanda, and the International Criminal Tribunal for the former Yugoslavia. The author argues that international proceedings have seen the emergence of a new type of evidence: a cognitive, linguistic, culturally determined plural of genocidal mens rea . As a result, the mental element of genocidal intent can neither be interpreted nor understood without an advanced forensic approach to the language used by the network of génocidaires. Based on a combination of cognitive and social science research with the humanities, the article applies a hybrid method of analysis to some of the genocide cases in international criminal justice and demonstrates how and why this approach ought to be introduced into the process of identification of the guilty minds of the architects of genocide.